Synergistic effects of the capsaicinoid nonivamide and rosuvastatin on obesity-related endothelial dysfunction in rat fed a high-fat diet - Sivanan Sivasinprasasn (2019)
© 2019 John Wiley & Sons, Ltd. Capsaicinoid nonivamide (PAVA) and rosuvastatin (RSV) have been shown to exert antioxidant and anti-obesity effects in various animal models, but it is unknown whether their combination would be an effective treatment for obesity-related endothelial dysfunction. This study aimed to investigate the mechanism of PAVA in synergy with RSV. Male Sprague–Dawley rats were given a high-fat diet (HFD) or normal diet during a 20-week period. At 16 weeks, rats in each diet group were divided into subgroups. Normal diet rats were divided into Normal diet control, Normal diet with PAVA, and Normal diet with RSV groups. HFD rats were subdivided into HFD control, HFD with PAVA, HFD with RSV, and HFD with PAVA + RSV groups and evaluated for metabolic parameters, blood pressure, aortic function, and histological change of the aorta in rats. Our results showed the combined therapy had a significantly greater effect than the monotherapy in all measured parameters; this was indicated by improvement in insulin sensitivity and aortic function, decreased blood pressure, lower oxidative stress, and prevention of vascular damage. The synergistic effect of the PAVA and RSV can protect HFD-induced obesity-related endothelial dysfunction, suggesting that the combination of PAVA and RSV could be an effective alternative treatment for obesity-related complications in patients with cardiovascular disease.